The Shift in Understanding and Interpretation of the Assassination of Governor Soeryo in 1948 Between Two Generations in Ngawi Regency, East Java - Sunandar Priyo Santoso; Ganda Febri Kurniawan (JURNAL PENDIDIKAN IPS, 2025)
The understanding and interpretation of a historical event will inevitably change over time. This shift is closely related to the cultivation of collective memory within each generation, shaped by the knowledge they acquire. This study aims to explore the various understandings and interpretations held by both younger and older generations regarding the incident of the assassination of Governor Suryo in Ngawi Regency, East Java. This research employs a qualitative method with a phenomenological approach, with primary data obtained through interviews conducted in Kauman Village, Widodaren District, and in Planggarem and Planglor Villages, Sidolaju District, Ngawi Regency, from May 11 to 17, 2025. The results of the study indicate a clear shift in understanding and interpretation between the older and younger generations. The older generation possesses a deeper understanding due to their geographical proximity, direct experiences, and the continuation of oral traditions. They interpret this historical event as part of a heritage and a symbol of struggle that must be preserved. On the other hand, the younger generation tends to have a more superficial understanding, primarily gained through formal education and social media, and tends to interpret the event functionally, using it as a moral lesson and a rational approach to fostering nationalism. This generational shift has contributed to a declining concern for the preservation of monuments and local historical traditions. This study highlights the importance of strengthening local historical literacy and implementing local history education interventions to ensure the continuity of collective memory within society and to foster intergenerational nationalism.